Development of accelerated wet–dry cycle corrosion test in marine environment for weathering steels. (25th October 2015) - Artigas, A.; Monsalve, A.; Sipos, K.; Bustos, O.; Mena, J.; Seco, R.; Garza-Montes-de-Oca, N.
Abstract : There is great interest in the steel industry of incorporating new products that go beyond the properties of existing ones. Among these properties, corrosion resistance is extremely important for countries that, like Chile, have an extensive ocean coastline. In costal zones, the chloride ions in air produce corrosion that reduces the service life of structures. For this reason, it is of utmost importance to study the influence of different alloying elements such as nickel, which lead to improve steel's resistance to marine corrosion. In this context the development of new types of steel is hindered if the evaluation of their corrosion resistance takes very long times. This paper presents a methodology based on accelerated wet–dry cycle corrosion experiences to simulate the behaviour of steel over time in a marine environment. The results of the proposed methodology allow adequate prediction of corrosion thickness in ASTM A242 and A588 steels exposed for years to a specific marine environment.